Monogenic developmental and epileptic encephalopathies of infancy and childhood, a population cohort from Norway - Stenshorne, Ida; Syvertsen, Marte; Ramm-Pettersen, Anette; Henning, Susanne; Weatherup, Elisabeth; Bjørnstad, Alf; Brüggemann, Natalia; Spetalen, Torstein; Selmer, Kaja K.; Koht, Jeanette (Frontiers in Pediatrics, 2022)
Introduction Developmental and epileptic encephalopathies (DEE) is a group of epilepsies where the epileptic activity, seizures and the underlying neurobiology contributes to cognitive and behavioral impairments. Uncovering the causes of DEE is important in order to develop guidelines for treatment and follow-up. The aim of the present study was to describe the clinical picture and to identify genetic causes in a patient cohort with DEE without known etiology, from a Norwegian regional hospital. Methods Systematic searches of medical records were performed at Drammen Hospital, Vestre Viken Health Trust, to identify patients with epilepsy in the period 1999–2018. Medical records were reviewed to identify patients with DEE of unknown cause. In 2018, patients were also recruited consecutively from treating physicians. All patients underwent thorough clinical evaluation and updated genetic diagnostic analyses. Results Fifty-five of 2,225 patients with epilepsy had DEE of unknown etiology. Disease-causing genetic variants were found in 15/33 (45%) included patients. Three had potentially treatable metabolic disorders (SLC2A1, COQ4 and SLC6A8). Developmental comorbidity was higher in the group with a genetic diagnosis, compared to those who remained undiagnosed. Five novel variants in known genes were found, and the patient phenotypes are described. Conclusion The results from this study illustrate the importance of performing updated genetic investigations and/or analyses in patients with DEE of unknown etiology. A genetic cause was identified in 45% of the patients, and three of these patients had potentially treatable conditions where available targeted therapy may improve patient outcome.